Non-ketotic hyperglycaemia induced occipital reflex focal seizures - Buque, Helena (2023)
A myriad of neurological manifestations can occur in association with ketotic and non ketotic hyperglycaemic states. Contrary to diabetic coma, which is a universal complication under relatively established metabolic circumstances, the pathophysiology beyond hyperglycaemicassociated positive neurological manifestations, including seizures, remains to be elucidated. The occurrence of symptomatic focal epilepsy as a manifestation of diabetes-related hyperglycaemia is seldom reported. Herein, we present a case of focal epilepsy with alternating positive and negative neurological manifestations as the initial manifestation of diabetes-related hyperglycaemia. The electroencephalogram confirmed the diagnosis of focal occipital seizures, and the brain magnetic resonance imaging depicted the associated typical transient imaging findings in the occipital lobe. Seizures were refractory to antiepileptics, and symptomatic control was achieved after achieving normoglycemia. On follow-up, complete clinical and imaging recovery occurred. Reflex focal epilepsy in the context of hyperglycaemic states is a rare condition, and the possibility of misdiagnosis is likely high. As reported in similar cases, seizures can be resistant to antiepileptics. An important message to highlight is that seizures associated with hyperglycaemic status can be resistant to antiepileptic treatment and only cease with glycaemic control.